ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN MARGIN MURABAHAH BANK UMUM SYARIAH DI INDONESIA DENGAN NPF SEBAGAI VARIABEL MODERASI - MALINDA IRIANI (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2018)
Abstract Murabahah margin income is the highest income generated by Islamic banking. This study aims to determine what factors influence murabahah margin income. The variables examined in this study are DCMR, ICMR, ECRI, acquiring cost, and overhead costs and Non Performing Financing as moderating variables. The data used is secondary data, coupled with the results of literature studies. Data analysis using moderation multiple linear regression method. The conclusions of this study are: (1) Simultaneously DCMR, ICMR, ECRI, Acquiring Cost, and Overhead Cost affect murabahah margin income, (2) partially DCMR, ICMR, ECRI, Acquiring Cost, and Overhead Cost have an influence on margin income Murabahah Sharia Commercial Bank in Indonesia in the following quarter. (3) NPF affects murabahah margin income and moderates the variables DCMR, ICMR, ECRI, Acquiring Cost, and Overhead Cost